Providing Education and Breastfeeding Assistance in Efforts to Increase Exclusive Breastfeeding - Anuhgera, Diah Evawanna; Jalilah, Nikmah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Breastfeeding is important for growth and development, especially in the first 6 months. Exclusive breastfeeding has the benefit of protecting against gastrointestinal, respiratory, chronic diseases and helping cognitive development. The practice of exclusive breastfeeding requires knowledge, skills and confidence in breastfeeding. Breastfeeding assistance is one of the actions that midwives can provide to mothers in helping and supporting the success of breastfeeding. The purpose of this service is to provide increased knowledge to breastfeeding mothers through education and breastfeeding assistance in theory and correct skills in increasing the provision of exclusive breastfeeding.. The methods used are lectures and demonstrations. The target of this activity is postpartum mothers from day 1 to day 4 who gave birth at the Kasih Ibu Pratama Clinic, a total of 19 postpartum mothers. Evaluation of the activity was carried out by providing pre- and post-test questionnaires and assessing the mother's skills in breastfeeding. The results of this activity are an increase in knowledge, attitudes and beliefs about breastfeeding in mothers after being given breastfeeding assistance. It is expected that midwives can maximize breastfeeding support classes for pregnant women as a planning for the future breastfeeding process and for breastfeeding mothers to guide mothers in good and consistent breastfeeding practices in achieving exclusive breastfeeding.